KITES AS SYMBOLS IN BALINESE KARAWITAN MUSIC NEW CREATIONS: DECONSTRUCTING THE KITE TRADITION - Agus Eko Sattvika, I Putu; Ruastiti, Ni Made; Gede, Yoga Kharisma Pradana (Institut Seni Indonesia Denpasar, 2025)
In Balinese gamelan art, a new Balinese musical creation featuring kites has been introduced. While kite-flying traditions had previously existed, there had been no Balinese gamelan musical works featuring. This phenomena reflects a transformational style that involves deconstructive techniques. The concerns are: 1) What is the shape of new kite building in Balinese karawitan art activities?; 2) Are there differences in kite traditions & in Balinese karawitan art activities?; 3) What is the purpose of deconstruction of kite traditions in Balinese karawitan art activities?. A qualitative methods was applied from a cultural studies standpoint. An interdisciplinary strategy was used to collect all data, which included document studies, participant observation, and interviews with Karawitan artists. All data were analyzed qualitatively-interpretively, with consideration given to deconstruction, aesthetics, and ethnomusicology theories. The results show tha t: 1) a new construction of kite tradition elements is seen in the sound patterns of new creative karawitan music; 2) the form of kite tradition is seen in the phase preceding the realization of new creative karawitan music works with a kite theme; and 3) artistic, religious, and communicative meanings are implied in the new creative karawitan artworks as a deconstruction of the kite tradition. These discoveries help to shape karawitan art based on local wisdom and create opportunity for discussion amongst traditional cultural forms.